Analysis of LED wire bonding during encapsulation process. Issue 1 (December 2020) - Roslan, Hafiz; Abdul Aziz, M.S.; Abdullah, M.Z.; Kamarudin, R.; Ishak, M.H.H.; Ismail, F.; Purna Irawan, Agustinus
Abstract: The encapsulation process is crucial since its act as first layer protection for the LED. The encapsulation process also influences the quality of the product. The structure of the encapsulate will affect the quality of emitting light in term of brightness and color. Thus, the process of encapsulation is one of the factors that can improve the quality of the product. This study aimed to observe the encapsulation process of LED and the interaction between gold wire bonding and EMC. By considering the computational method using Fluid-Structure Interaction (FSI), the VOF was used to simulate the dispense of EMC during the encapsulation process. Besides, an experiment was conducted to validate the simulation result. Thus, the FSI was utilized to predict the amount of stress on to the gold wire bonding during the encapsulation process. The broken gold wire bonding that connects these two elements indirectly will cost the failure of the product to work as intended.